Weighted Bayesian Belief Network for diabetics: a predictive model - Kharya, Shweta; Soni, Sunita; Pati, Abhilash; Panigrahi, Amrutanshu; Giri, Jayant; Qin, Hong; Mallik, Saurav; Nayak, Debasish Swapnesh Kumar; Swarnkar, Tripti (Frontiers in Artificial Intelligence, 2024)
Diabetes is an enduring metabolic condition identified by heightened blood sugar levels stemming from insufficient production of insulin or ineffective utilization of insulin within the body. India is commonly labeled as the "diabetes capital of the world" owing to the widespread prevalence of this condition. As of my last knowledge update in September 2021, approximately 77 million adults in India were reported to be affected by diabetes, reported by the International Diabetes Federation. Owing to the concealed early symptoms, numerous diabetic patients go undiagnosed, leading to delayed treatment. While Computational Intelligence approaches have been utilized to improve the prediction rate, a significant portion of these methods lacks interpretability, primarily due to their inherent black-box nature. Rule extraction is frequently utilized to elucidate the opaque nature inherent in machine learning algorithms. So, to resolve the Black box nature, a method for extracting strong rules based on Weighted Bayesian Association Rule Mining is used so that the extracted rules to diagnose any disease like diabetes can be very transparent and easily analyzed by the clinical experts, enhancing the interpretability. The WBBN model is constructed utilizing the UCI machine learning repository, demonstrating a performance accuracy of 95.8%.